Multi-level governance - Bache, Ian; Flinders, Matthew V. (Oxford University Press, 2004)
'Multi-Level Governance' analyses the ways in which the concept has been applied across different academic and policy territories.
Keywords: Decentralization in government -- European Union countries.; Regionalism -- European Union countries.; Central-local government relations -- European Union countries.; Regionalism (International organization); European Union -- Great Britain.; Decentralization in government -- Great Britain.; Central-local government relations -- Great Britain.; Regionalism -- Great Britain.; Régionalisme -- Pays de l'Union européenne.; Relations gouvernement central-collectivités locales -- Pays de l'Union européenne.; Régionalisme (Politique internationale); Relations gouvernement central-collectivités locales -- Grande-Bretagne.; Régionalisme -- Grande-Bretagne.; POLITICAL SCIENCE -- Civics & Citizenship.; Central-local government relations; Decentralization in government; Regionalism; European Union countries; Great Britain; Supranationalität; Regionalprinzip; Governance; Nationalstaat; Openbaar bestuur.; Decentralisatie.; Europese integratie.; Onderzoeksmethoden.; Electronic books.; Kongress.; Sheffield (2001)